The Color of Work: The Struggle for Civil Rights in the Southern Paper Industry, 1945-1980 - Nelson, Bruce (Labour / Le Travail, 2004)
The article reviews the book, "The Color of Work: The Struggle for Civil Rights in the Southern Paper Industry, 1945-1980," by Timothy J. Minchin.